Combined Effect of Shegandilong Granule and Doxycycline on Immune Responses and Protection Against Avian Infectious Bronchitis Virus in Broilers - Feng, Haipeng; Wang, Xuezhi; Zhang, Jingyan; Zhang, Kang; Zou, Wenshu; Zhang, Kai; Wang, Lei; Guo, Zhiting; Qiu, Zhengying; Wang, Guibo; Xin, Ruihua; Li, Jianxi (Frontiers in Veterinary Science, 2021)
Infectious bronchitis (IB) causes significant economic losses to commercial chicken farms due to the failures of vaccine immunization or incomplete protection. In this study, we evaluated the effect of a combination therapy consisting of Shegandilong (SGDL) granule (a traditional Chinese veterinary medicine) and doxycycline (Dox) on immune response and the protection in broilers infected with IBV. A total of 144, 7-day old broilers were randomly divided into four groups after vaccination. Group I served as a control. Broilers in Group II were given Dox whereas Group III was given SGDL granule through drinking water. Broilers in Group IV were given SGDL granule and Dox by drinking water. Broilers in all groups were challenged with IBV through intraocular-and-intranasal routes at day 28. Results showed anti-IBV antibody level was higher in group IV compared with the level in other groups. Immunohistochemistry and ELISA results showed an increase in Immunoglobulin A (IgA) level was observed in the trachea with the maximum level observed at day 14. In addition, SGDL granule + Dox effectively inhibited IBV replication and stopped IBV propagation from trachea to lung, modulated mRNA expression of IL-1β, IL-6, TNF-α, IFN-γ and extenuated histopathology lesions in trachea and lung. These data imply that a combination of SGDL granule and doxycycline is effective in preventing IB outbreaks in commercial poultry farms.